Karakteristik limbah dan dampaknya bagi kesehatan pembatik di Lendah, Kulon Progo - Suhartini - suhartini; Sri Awalia Febriani; IBG. Surya Putra Pidada; Hendro Widagdo; Martiana Suciningtyas; Yudha Nurhantari; Dewanto Yusuf Priyambodo; Agus Surono; Roto Roto; Geraldine Nadita Putri Kinasih; Pramudji Hastuti; Sri Sutarni (Journal of Community Empowerment for Health, 2019)
Synthetic batik coloring often uses heavy metals element such as lead (Pb), chromium (Cr),silica (Si), and hydrochloric acid (HCl). The exposure of heavy metals in long period results in health impair on the artisans and eventually harming the environment. The purpose of this research is to analyze the waste characteristics and health impact towards the artisans in the Lendah, Kulon Progo. Seventy-six batik artisan, consisting of 37 from SB, 20 from FA, and 19 from SA underwent 5 ml blood sampling. The samples were used to determine their hemoglobin (Hb) level, packed cell volume (PCV), blood sugar, and total cholesterol. Blood plasma and wastewater were examined for Pb and Cr using the inductively coupled plasma (ICP) method; Si using atomic absorption spectrophotometry (AAS); and Cl- using spectrophotometry. Respondents underwent health checks and were interviewed about the impact of waste and disease complaints experienced using a questionnaire. Cognitive disorders were examined using mini-mental state examination (MMSE) and peripheral neuropathy was assessed using diabetic neuropathy symptom (DNS) score. The results obtained were analyzed by analysis of variance and t-test. Correlation test was used to examine the relationship of Pb and Cr with cognitive disorders. Total cholesterol levels and blood sugar were analyzed descriptively. There is no difference in knowledge about waste in batik makers in SB, FA, and SA. The level of Pb, Cr, and Cl- within the three production centers showed no significant difference (p > 0,05), whilst Si level showed significant difference between centers (p < 0,05). There is no correlation between Pb and Cr blood levels with cognitive impairing according to MMSE and occurence of peripheral neuropathy according to DNS score (p > 0.05). Normal cholesterol levels (< 200mg/dL) andnormal blood glucose levels (< 200 mg/dL) were observed in 70.0-80.5% and 85.0-95.1% batik artisans, respectively. Si levels in all three production centers’ waste shows significant difference. The most frequent complaint was back pain and dizziness. There is no correlation caused by Pb and Cr levels toward cognitive impairing. Cholesterol level in batik artisans tended to be high.